2018
DOI: 10.1212/wnl.0000000000005354
|View full text |Cite
|
Sign up to set email alerts
|

Memory decline accompanies subthreshold amyloid accumulation

Abstract: Memory decline accompanies Aβ accumulation in otherwise healthy, Aβ-negative older adults. Amyloid increases within the negative range may represent the earliest detectable indication of pathology with domain-specific cognitive consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
116
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 32 publications
15
116
0
Order By: Relevance
“…This has no impact on the conclusion of the article, especially as our results remained unchanged when excluding the "intermediate" cases (who did not differ anymore from the controls in terms of florbetapir binding when compared voxelwise; see Supplementary Material). Yet, this further supports the relevance of subthreshold amyloid accumulation [47][48][49][50][51]. Differences in the samples (sample size or degree of cognitive impairment) could also explain the discordances between studies.…”
Section: Discussionsupporting
confidence: 64%
“…This has no impact on the conclusion of the article, especially as our results remained unchanged when excluding the "intermediate" cases (who did not differ anymore from the controls in terms of florbetapir binding when compared voxelwise; see Supplementary Material). Yet, this further supports the relevance of subthreshold amyloid accumulation [47][48][49][50][51]. Differences in the samples (sample size or degree of cognitive impairment) could also explain the discordances between studies.…”
Section: Discussionsupporting
confidence: 64%
“…Although there are established positron emission tomography and cerebrospinal fluid (CSF) beta-amyloid (Aß) and tau biomarkers, both are costly and invasive. Moreover, several studies have found cognitive function to be an earlier predictor of disease progression than currently defined biomarkers [4][5][6][7][8][9] . Development of additional, non-invasive markers of risk that might tap some aspect of the disease process even earlier might aid in prediction.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, this effect was not associated with Aβ burden and was already observed in mutation carriers who did not reach Aβ-positivity, suggesting that accelerated functional brain aging occurs before Aβ accumulation can be detected using PET imaging. While we cannot exclude the fact that some Aβ negative individuals would in fact be Aβ accumulators [49][50][51] or present other forms of Aβ that cannot be detected through PET, this could also suggest that mutated genes have life-long effects on the brain that are not fully dependent on Aβ accumulation. Consistently, a previous study in PSEN1 mutation carriers from the Columbian cohort showed early changes in brain function before evidence of cerebral Aβ plaque accumulation.…”
Section: Discussionmentioning
confidence: 95%